Effect of Multiple Types of High-fat Diet Induction on Gut Microbiota Profile and Butyrate Levels on NAFLD Rat Model: High-fat Diet Induction on Gut Microbiota Profile and Butyrate Levels - Syifa Mustika; Nabila Ramadhani; Novita Apramadha Kartika Sari; Dian Handayani; Dewi Santosaningsih (Journal of Tropical Life Science, 2024)
Dysbiosis, marked by a decline in Firmicutes (such as Clostridium spp.) and a rise in Proteobacteria (such as Escherichia coli), is recognized as a pathway linked to the progression of non-alcoholic fatty liver disease (NAFLD). High-fat food may influence the development of NAFLD. This study investigates the effect of different high-fat diets on gut microbiota composition and butyrate levels in a rat model. Four groups of Rattus norvegicus strain Wistar (n=27) were fed specific diets for 12 weeks: normal diet (ND, n=7), high-fat diet (HFD, n=6), western diet (WD, n=7), and high-fat-high-fructose diet (HFHFD, n=7). Stools were cultured on Eosin Methylene Blue (EMB) for Escherichia coli and Forget Fredette Agar (FFA) for Clostridium spp. Colonies were counted using Total Plate Count (TPC), and butyrate levels were measured with gas chromatography. Liver histology was assessed with the NAFLD activity score (NAS). Gut microbiota were analyzed using Crosstab and Chi-Square tests, and butyrate levels with the Kruskal-Wallis test. Butyrate levels decreased in NAFLD-inducing diet groups (HFD, WD, HFHFD) compared to ND (p=0.021). Escherichia coli colony counts were significantly higher in NAFLD-inducing diet groups (p=0.048), while Clostridium spp. counts were higher in ND (p=0.001). Liver histological changes, particularly in the WD group, resembled NAFLD. These findings imply that different high-fat diets can alter the gut microbiome, potentially influencing NAFLD development.